POTENSI DAN PEMANFAATAN HASIL SAMPING INDUSTRI DAUN BELUNTAS (Potential and Utilization of Industry By-Product Beluntas Leaves) - Yusriani, Yenni; Asmairecen, Sharli; Djafar, Fitriana; Busthan, Meuthia (Baristand Industri Banda Aceh, 2016)
Beluntas leaf (Pluchea indica L. Less) is one byproduct of the agriculture industry is knownas effective agents for efficacious as an appetite enhancer and aid digestion which is expected to spurgrowth. Since the old times, as plant Beluntas is considered have ability believed to reduce body odor,reduce heat and other benefits. Beluntas leaves can be used as a source of antioxidants, anti-stress, antibacterial,anti-cancer, lowering cholesterol, lowering fever, deodorizing fishy. This is due to Beluntascontaining amino acid (leucine, isoleucine, tryptophan, threonine), alkaloids, flavonoids, essential oils,chlorogenic acid, sodium, potassium, aluminum, calcium, magnesium, phosphorus, iron, vitamins A and C.This paper is a revision of some of the results of research that has been done on the potential and utilizationof industrial by products Beluntas leaves.